PESAN-PESAN DAKWAH DALAM FILM JANGAN BUAT AKU BERDOSA (STUDI ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE) - Azizah, Adelia Nur; Fajar, M. Samson; Nur, Muhammad (Universitas Muhammadiyah Metro, 2021)
The message of da'wah is what is conveyed in the process of delivering da'wah. In communication, da'wah messages are also called messages, namely symbols. Film as a propaganda medium means a tool used in da'wah activities or an intermediary in delivering da'wah messages. Film is a powerful medium of communication, not only for entertainment, but also for education and information. In fact, Jakob Sumardjo, from the center for film and television education, stated that films act as experiences and values. It is very possible as a means of transmitting stimuli in society as well as to be used as a means of conveying Islamic symbols to the wider community. Because the film as a communication device, is able to absorb the communicant widely. An example of a film as a propaganda medium is the film Jangan Buat Aku Berdosa (Don't Make Me Sin), which is a short film made by the Jurnalis Pejuang of Pena Production (JP3) and directed by Gusti Adi Pranoto. 39 Minutes in duration, consisting of 3 episodes released on January 12, 2018 from screenwriter Fia Handari. The film Jangan Buat Aku Berdosa consists of 3 episodes. Each episode is titled Jangan Buat Aku Berdosa, Memantaskan Diri and Jika Karna-Nya. This film has also won an award as